1995
DOI: 10.1097/00003246-199504000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Decreased antioxidant status and increased lipid peroxidation in patients with septic shock and secondary organ dysfunction

Abstract: These data indicate decreased antioxidant status in the face of enhanced free radical activity, and suggest potential therapeutic strategies involving antioxidant repletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
239
2
14

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(269 citation statements)
references
References 20 publications
11
239
2
14
Order By: Relevance
“…The pathophysiological role of severe oxidative stress reactions in SIRS has been demonstrated by experimental and clinical studies, in which an increase in measured oxidative stress markers are directly associated with a decrease in serum antioxidants (5,20). In our study, we highlighted that increased levels of 8-OHdG/Creatinine as an oxidative stress marker correlated with increased levels of PCT, CRP and WBC.…”
Section: Discussionsupporting
confidence: 58%
“…The pathophysiological role of severe oxidative stress reactions in SIRS has been demonstrated by experimental and clinical studies, in which an increase in measured oxidative stress markers are directly associated with a decrease in serum antioxidants (5,20). In our study, we highlighted that increased levels of 8-OHdG/Creatinine as an oxidative stress marker correlated with increased levels of PCT, CRP and WBC.…”
Section: Discussionsupporting
confidence: 58%
“…The most seriously ill patients in intensive care units (ICUs) have increased mediators of oxidant stress and a higher incidence of multiorgan failure than less seriously ill patients. [1][2][3][4][5] Meta-analyses of randomized trials suggest that glutamine and antioxidant supplementation in critically ill patients may be associated with improved survival. 6,7 However, recent large studies have not confirmed such an effect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, albumin has an antioxidant effect, 40,41 and it is well known that oxidative stress is an important feature in the pathogenesis of sepsis. 42 We do not have an explanation for the second question.…”
Section: Discussionmentioning
confidence: 95%